Сущностные характеристики подходов квнутриклассной индивидуализации обучения младших школьников с синдромом Дауна - Савицкий, А. Н.
Concepts of the individualized training of children with a Down syndrome at inclusive education are covered in article. Psychomotor development of children with this genetic pathology and the related bases of education at younger school is in details considered. The basic methodological provisions of training of these children in the conditions of integration into general education educational inst itutions are defi ned.
Keywords: Дети с синдромом Дауна